SERR-spectroelectrochemical study of a cbb oxygen redutase in a biomimetic construct - Todorovie, Smilja (2008)
The chb3 oxygen reductase from Bradyrhizobium japonicum was immobilized on nanostructured silver electrodes by anchoring the enzyme via a His-tag to a Ni-NTA coating, followed by reconstitution of a lipid bilayer. The immobilized enzyme retains the native structure and catalytic activity as judged by in situ surface- enhanced vibrational spectroscopy and cyclic voltammetry, respectively. Spectroelectrochemical titrations followed by SERR spectroscopy of the integral enzyme and its monohemic (fixO) and dihemic subunits (fixP), allowed the determination of the reduction potentials for the different heme c groups. Both in the isolated subunits and in the integral enzyme the Met/His-coordinated hemes from the two subunits present identical reduction potentials of 180 mV, whereas for the bis-His heme from fixP the value is ca. 400 mV. The determination of reduction potentials of the individual hemes c reported in this work provides the basis for further exploring the mechanism of electroprotonic energy transduction of this complex enzyme.